ANTESEDEN DARI TEORI UTAUT DAN KONSEKUENSINYA (STUDI EMPIRIS PURCHASE INTENTION GENERASI Z) - Juniarty Juniarty; Verrell Valentinus Gunawan (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract - With the huge number of social media accesses today, many people are trying to develop their marketing strategies by using social media to influence consumer buying interest through advertisements on social media. The research purpose was to see the impact of the antecedents of theory technology acceptance and use, planned behavior on media social advertising on buying interest of z generation in Jabodetabek who are active in the use of media social with a total sample of 161 respondents. The technique used for distributing questionnaires is by distributing questionnaires online using a Likert scale. The data was processed using the SmartPLS program. Based on the examination, concluded that Interactivity influences Purchase Intention, Interactivity influences Performance Expectancy, Interactivity influences Hedonic Motivation, Informativeness influences Purchase Intention, Perceived Relevance influences Purchase Intention, Perceived Relevance influences Performance Expectancy, Performance Expectancy has no influence on purchase intention, Hedonic Motivation has no impact on Purchase Intention, Habit does not influence Purchase Intention, and Informativeness has no impact on Performance Expectancy. This research provide information to companies or organizations about the influence of advertising on social media to improve their customers' buying interest. This research also gives some limitations and recommendations for future researchers so that they can conduct better analysis in the future. Keywords: Hedonic Motivation; Interactivity; Perceived Relevance; Performance Expectancy; Purchase Intention